2016
DOI: 10.1159/000454881
|View full text |Cite
|
Sign up to set email alerts
|

Benzodiazepine Use and Risk of Dementia in the Elderly Population: A Systematic Review and Meta-Analysis

Abstract: Background: Benzodiazepines are a widely used medication in developed countries, particularly among elderly patients. However, benzodiazepines are known to affect memory and cognition and might thus enhance the risk of dementia. The objective of this review is to synthesize evidence from observational studies that evaluated the association between benzodiazepines use and dementia risk. Summary: We performed a systematic review and meta-analysis of controlled observational studies to evaluate the risk of benzod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
110
1
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 187 publications
(121 citation statements)
references
References 48 publications
7
110
1
3
Order By: Relevance
“…A recent meta‐analysis of 10 studies showed that the risk of developing dementia following long‐term BZD usage is 78% higher than for non‐BZDs users (Islam et al . ). Furthermore, a 9‐year longitudinal study linked long‐term use of diazepam with impairments in cognitive performance in elderly subjects (Bierman et al .…”
Section: Allosteric Modulators Of Gabaa Receptorsmentioning
confidence: 97%
“…A recent meta‐analysis of 10 studies showed that the risk of developing dementia following long‐term BZD usage is 78% higher than for non‐BZDs users (Islam et al . ). Furthermore, a 9‐year longitudinal study linked long‐term use of diazepam with impairments in cognitive performance in elderly subjects (Bierman et al .…”
Section: Allosteric Modulators Of Gabaa Receptorsmentioning
confidence: 97%
“…and H.-C.Y.) who are experts in drug and disease relationship research [13,[15][16][17][18]. The relevant electronic databases (e.g., PubMed, EMBASE, and Scopus) were searched for articles published between January 1, 1990 and November 1, 2017, which reported the possible association between psoriasis and MS risk.…”
Section: Data Sourcementioning
confidence: 99%
“…When the number of studies is not large, the visual interpretation and test for asymmetry of the funnel plot of the publications are not very reliable [15]. Figure 3 shows the funnel plot that indicates the existence of some publication bias.…”
Section: Publication Biasmentioning
confidence: 99%
“…In contrast, in their case control studies, Imfeld et al (2015) showed that BZD use was not associated with an increased risk of AD or vascular dementia. Three meta-analyses (Islam et al, 2016;Penninkilampi & Eslick, 2018;Zhong, Wang, Zhang, & Zhao, 2015) suggested that BZD use was significantly associated with an increased risk of dementia, and a dose-response association was highlighted by Zhong et al (2015). Furthermore, the final meta-analysis performed by Penninkilampi and Eslick (2018) only included studies that controlled for protopathic bias.…”
Section: Benzodiazepinesmentioning
confidence: 99%